Quantification of CO₂ Emission Reductions from Biomass Co-firing at a Coal-Fired Power Plant Using the IPCC 2006 Tier 2 Methodology - Tasdik Darmana; Khumaidah Darojat; Dyah Ayu Kesuma; Ariman Ariman; Veriah Hadi (Sean Institute, 2026)
Coal-fired power plants are the dominant source of electricity in Indonesia but also a major contributor to greenhouse gas (GHG) emissions, posing challenges to the country’s net-zero emission commitment by 2060. This study aims to quantify the impact of biomass co-firing on emission reduction and carbon credit potential in Pangkalan Susu, Kabupaten Langkat, North Sumatra Power Plant using the 2006 IPCC Guidelines (Tier 2). Operational data from 2022 (100% coal) and 2024 (coal–biomass mix) were analyzed through a mass and energy balance approach. Results indicate that integrating 41,324 tons of solid biomass and 3,798 kiloliters of liquid biomass in 2024 reduced coal consumption by 24,379 tons and cut CO₂ emissions by 38,419 tons compared to the 2022 baseline. Although the substitution rate was only 1.72% of the fuel mix, the reduction was measurable and economically significant, providing potential carbon credit value. These findings highlight biomass co-firing as a viable strategy to reduce GHG emissions and support Indonesia’s energy transition, while emphasizing the need for advanced methodologies (Tier 3, LCA) and sustainable biomass supply chains to ensure long-term implementation.